ENHANCING STUDENTS’ SPEAKING ABILITY THROUGH SELF TALK STRATEGY (STS) - Naily Mufidatul Azka; Ririn Ambarini; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The primary aims of this study were to assess the improvement in students' speaking skills following the implementation of the Self Talk Strategy (STS) and to evaluate the outcomes of teaching students' speaking achievement both before and after the utilisation of the Self Talk Strategy (STS). The present study employed a quantitative approach and utilised a pre-experimental design with a single group, employing both pre-test and post-test assessments. The population for this study consisted of 10th grade students from SMA Negeri 3 Pemalang. A sample of 34 students was selected from class X.5 to represent the population. The research instrument utilised in this study was a spoken test, which consisted of a pre-test and a post-test. The findings of the data analysis revealed statistically significant disparities between the pre-test and post-test scores of the students. The mean score for speaking students on the post-test (M = 12.82) was found to be significantly higher than their pre-test score (M = 10.06). Furthermore, the t-score is considered to be smaller than the critical value from the t-table at a significance level of 0.05%. The alternative hypothesis (Ha) was deemed statistically significant, leading to the rejection of the null hypothesis (H0). The findings suggest a notable change in the students' classroom discourse patterns pre- and post-implementation of the self-talk method. Based on the findings and subsequent discussion of the research, it was determined by the researcher that the implementation of the Self-Talk Strategy (STS) resulted in an enhancement of the students' oral communication skills.